Enhancing SWAT+ simulation of groundwater flow and groundwater-surface water interactions using MODFLOW routines. (April 2020) - Bailey, Ryan T.; Park, Seonggyu; Bieger, Katrin; Arnold, Jeffrey G.; Allen, Peter M.
Abstract: This paper presents a version of SWAT + that uses MODFLOW to simulate groundwater flow and groundwater-surface interactions within a watershed system. The modeling code is applied to the 470 km 2 Middle Bosque River Watershed (Texas, USA) to demonstrate accuracy and differences with SWAT+. The model is tested against field-measured stream discharge, groundwater levels and fluctuation patterns, runoff, baseflow, recharge, watershed boundary groundwater flow, groundwater-surface water interactions, and evapotranspiration. The model captures the dominant baseflow patterns throughout the watershed and the key patterns of water table dynamics and relation to nearby streams. Whereas annual rates of runoff, lateral flow, and annual percolation are unchanged from a stand-alone SWAT + simulation, annual groundwater discharge rates increase by 50% (37 mm–54 mm). In particular, temporal patterns of groundwater discharge are governed by the physically-based rise and fall of groundwater near streams, rather than storm-induced recharge pulses as in the SWAT + simulation. Highlights: We present a revised version of SWAT + that includes MODFLOW routines. SWAT+(MODFLOW) simulates spatially-distributed groundwater flow. SWAT+(MODFLOW) is tested in a 470 km 2 watershed in central Texas, USA.